Building Pyridinium Molecular Wires as Axial Ligands for Tuning the Electrocatalytic Activity of Iron Phthalocyanines for the Oxygen Reduction Reaction - Zagal-Moya, J; Zagal-Moya, J; Caroli-Rezende, M; Silva-Rojas, J; Silva-Rojas, J; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Berrios-Guinez, C; Ponce-Hormazabal, I; Onate, R; Gutierrez-Ceron, C; Gutierrez-Ceron, C (American Chemical Society, 2018)
We have been able to "tune" the electrocatalytic activity of iron phthalocyanine (FePc) and iron hexadodecachlorophthalocyanine (16(Cl)FePc) for the oxygen reduction reaction (ORR) by manipulating the "pull effect" of pyridinium molecules axially bounded to the phthalocyanine complexes (FePcs). These axial ligands play both the role of molecular anchors and also of molecular wires. The axial ligands also affect the reactivity of the Fe metal center in the phthalocyanine. The "pull effect" originates from the positive charge located on the pyridinium core. We have explored the influence of the core positions (Up or Down), in two structural pyridiniums isomers on the activity of FePc and 16(Cl)FePc for the ORR. Of all self-assembled catalysts tested, the highest catalytic activity was exhibited by the Au(111)/Up/FePc system. XPS measurements and DFT calculations showed that it is possible to tailor the FePc-N(pyridiniums) Fe-O2 binding energies, by changing the core positions and affecting the "pull effect" of pyridiniums. This affects directly the catalytic activity of FePcs. The plot of activity as (log I)E versus the calculated Fe-O2 binding energies gives an activity volcano correlation, indicating that an optimum binding energy of O2 with the Fe center provides the highest activity. © 2018 American Chemical Society.